Game-theoretical frequency reuse algorithm in Femtocell network - Xiong ZHOU; Sui-li FENG; Yue-hua DING; Yong-zhong ZHANG (Tongxin xuebao)
A game-theoretical frequency reuse algorithm has been proposed for Femtocell network.Firstly,each Femtocell tries to get an available sub-band by sensing its radio circumstance.Then,inner-cluster frequency collisions are avoided by implementing a negotiation mechanism.Lastly,each cluster is regarded as a game player to get the largest utility by using its optimal strategy.Despite Femtocell base stations are randomly installed by users,the proposed method performs well in Femtocell network.Simulation results show that frequency collisions are dramatically reduced and the average capacity of Femtocells is considerably enhanced.